Razor Clams (Class Bivalvia) of Kuala Selangor, Malaysia: Morphology, Genetic Diversity and Heavy Metal Concentration - Hassan, Ruhana; Kanakaraju, Devagi (Borneo Journal of Resource Science and Technology, 2016)
Razor Clam (Bivalvia) could be easily identified as having two long, narrow shell valves connected by hinges, two siphons and one strong foot. It plays important role in ecological services besides providing food and extra income for the coastal communities. As filter feeder, razor clam is a good indicator for heavy metal contamination in aquatic environments. In Selangor, razor clam is locally known as ‘siput buluh’, yet, there is no proper scientific documentation on this species. This short study was carried out to assess the morphology of razor clams in Selangor for species identification and to sequence the Cytochrome Oxidase I (COI) gene for determination of its genetic diversity. Heavy sea traffics occurred in the sea near to the mudflat where razor clams were abundantly found has raised question whether razor clams were safe to be consumed. Therefore, this study is also designed to determine the level of selected heavy metals concentration in different body parts of razor clams. Based on selected morphometric and meristic data, razor clams of Kuala Selangor obtained during this study were Solen sarawakensis although many individuals displayed darker outer shell colouration and slightly thicker, longer and heavier shells. Based on analyses of putative COI gene sequences of approximately 677bp, there was a strong genetic divergence (11.7%) between S. sarawakensis inhabiting Kuala Selangor and Kuching Bay, Sarawak suggesting that although both razor clams were very similar morphologically, they could actually be two different species. Tissues of razor clams sampled from mudflat area in Kuala Selangor showed high concentration of Fe (146.50 mg/kg) and Mn (94.00 mg/kg). Other heavy metal elements namely Cr (42.50 mg/kg) and Cd (33.00 mg/kg) were also recorded during this study, occurring mainly in the shells. Traces of Hg were also detected, and its concentration did not differ much among the different parts analyzed.